Do macro ao micro: o papel da produtividade no desenvolvimento econômico - Corrêa, Vinicius Sampaio (2017)
This work emphasizes the evolution in the understanding of productivity as a fundamental factor for economic development. Based on a diagnosis that places productivity as a preponderant factor in determining the dispersion of income across countries, different approaches are presented in order to better understand the most elementary and fundamental mechanisms that determine it, focusing on the recent literature of misallocation. In order to achieve this aim, some of the main aspects identified as potential sources of poor resource allocation and the respective mechanisms through which they act are presented, together with some key empirical results. In addition, based on this theoretical framework, this text proposes a brief reflection about the way these mechanisms affect brazilian productivity and presents some reforms - already concluded or still under analisys - that aim to address some of the distortions observed in this economy.